'Shut Up! You Can't Even Read Latin!' Ancient Greek and Roman Material in Natsume Sōseki's I am a Cat. - Townshend, James R. (International Journal of the Classical Tradition, 2024)
This paper examines the sources and literary function of references to the ancient Greeks and Romans in the Japanese author Natsume Sōseki's first novel, I am a Cat, written and published from 1905 to 1907. It places Sōseki and his work in the context of Meiji Japan and its renewed engagement with the West. The paper shows how Sōseki was uniquely placed to reflect on this engagement, particularly its intellectual and literary aspects. Despite his personal familiarity with Greek and Roman materials as demonstrated in his scholarly works and notes, the references in his novel are mediated, drawn primarily from other (mainly English) texts rather than ancient sources. This reflects the most common manner of encountering this material for Sōseki's contemporary readership and therefore sheds some light on the diffusion of Greek and Roman material among the 'educated elite'. The paper further demonstrates that Sōseki's use of this material has literary and thematic point: it contributes to his satire of the emerging class of intellectuals in the Meiji period by critiquing the social weaponization of such knowledge, especially in instances where it is not backed by true understanding. The mediated nature of the Greek and Roman material in the novel also raises questions about the efficacy of language as a means of communication as it contributes to the destabilization of meaning. This is most noticeable in Sōseki's discussion of Greek and Latin language.